Endobronchial Aspergilloma Associated with Idiopathic Pulmonary Fibrosis: A Case Report and Review of the Literature - Li, Qiu-hong; Su, Yi-liang; Hou, Li-kun; Zhang, Yuan; Hu, Yang; Shen, Li; Zhang, Fen; Zhou, Ying; Li, Hui-Ping (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Not available